2020
DOI: 10.1002/1878-0261.12796
|View full text |Cite
|
Sign up to set email alerts
|

CircFNDC3B sequestrates miR‐937‐5p to derepress TIMP3 and inhibit colorectal cancer progression

Abstract: Circular RNA (circRNA) are single-stranded RNA with covalently closed 3 0 and 5 0 ends, with many recognized to be involved in human diseases as gene regulators, typically by interacting with other RNA. CircFNDC3B is a circRNA formed by back-splicing of exons 5 and 6 of the FNDC3B gene. CircFNDC3B was recently implicated in renal carcinoma, gastric and bladder cancer. However, the expression levels of circFNDC3B and its role in colorectal cancer (CRC) remain unclear. Expression of circFNDC3B and TIMP3 levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 49 publications
(67 reference statements)
0
54
0
Order By: Relevance
“…Using target prediction tools, we found that many of the protein-coding gene expression changes induced by PART1 are linked to changes in miRNAs. In addition to known effects on miR-190-3p , we report novel PART1 -mediated regulation of miR-937-5p , miR-22-5p , and miR-30b-3p in TNBC; all of which have been implicated in cancer progression in prior studies [ 71 , 72 , 73 , 74 , 75 ]. Additionally, we found that PART1 regulates miR-6870-5p ; however, in contrast to the miRNAs listed above, miR-6870-5p has not been studied previously and its function remains uncharacterized.…”
Section: Discussionmentioning
confidence: 68%
“…Using target prediction tools, we found that many of the protein-coding gene expression changes induced by PART1 are linked to changes in miRNAs. In addition to known effects on miR-190-3p , we report novel PART1 -mediated regulation of miR-937-5p , miR-22-5p , and miR-30b-3p in TNBC; all of which have been implicated in cancer progression in prior studies [ 71 , 72 , 73 , 74 , 75 ]. Additionally, we found that PART1 regulates miR-6870-5p ; however, in contrast to the miRNAs listed above, miR-6870-5p has not been studied previously and its function remains uncharacterized.…”
Section: Discussionmentioning
confidence: 68%
“…It has been reported that circFNDC3B contributes to the invasion and migration by modulating CD44 and E-cadherin expression in gastric cancer cells ( 29 ). CircFNDC3B serves as a sponge of miR-937-5p to regulate TIMP3 expression and in colorectal cancer development ( 30 ). CircFNDC3B modulates renal cancer by down-regulating miR-99a expression ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…circ-ERBB2 interacting protein (ERBIN), which derives from exons 2 to 4 of the ERBIN gene, promotes angiogenesis, proliferation, invasion and migration of CRC cells by targeting miR-125a-5p and miR-138-5p; this sponging effect increases eIF4E-binding protein 1 expression, which then increases hypoxia inducible factor-1α (HIF-1α) translation and activates the HIF-1α signaling pathway ( 80 ). Zeng et al ( 81 ) revealed significantly decreased expression levels of circ-fibronectin type III domain containing 3B (FNDC3B) in CRC tissues, cell lines and exosomes. Functional experiments indicated that overexpression of circFNDC3B suppressed CRC angiogenesis, which could be reversed by overexpression of miR-937-5p ( 81 ).…”
Section: Circrnas Are Involved In Angiogenesismentioning
confidence: 99%
“…Zeng et al ( 81 ) revealed significantly decreased expression levels of circ-fibronectin type III domain containing 3B (FNDC3B) in CRC tissues, cell lines and exosomes. Functional experiments indicated that overexpression of circFNDC3B suppressed CRC angiogenesis, which could be reversed by overexpression of miR-937-5p ( 81 ). Furthermore, it was demonstrated that tumor growth, angiogenesis and liver metastasis were suppressed by overexpression of circFNDC3B or circFNDC3B-exosome treatment ( 81 ).…”
Section: Circrnas Are Involved In Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation